2023
DOI: 10.1007/s43994-023-00031-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of different solvents on extraction yield, phenolic composition, in vitro antioxidant and antibacterial activities of deseeded Opuntia stricta fruit

Abstract: Opuntia stricta the shrubby plant is naturally occurring in all parts of the world used as popular ornamental and is known to have medicinal properties due to its phytochemical compositions. In this study, the effect of solvents (80% ethanol, 80% methanol and 80% acetone (v/v) in water) on the extraction yield, total phenolic content (TPC), total flavonoid content (TFC), antioxidant activity and antibacterial activity of Opuntia stricta fruit were investigated. For the antioxidant activity assay, three differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…Moreover, the results demonstrated that bioactive compound contents were affected by solvent polarity and varied from one part to another. This verified what is described in the literature, the solvent with higher polarity extracted more bioactive compounds that are responsible for several bioactivities [14][15][16].…”
Section: Bioactive Compounds Contentssupporting
confidence: 91%
“…Moreover, the results demonstrated that bioactive compound contents were affected by solvent polarity and varied from one part to another. This verified what is described in the literature, the solvent with higher polarity extracted more bioactive compounds that are responsible for several bioactivities [14][15][16].…”
Section: Bioactive Compounds Contentssupporting
confidence: 91%
“…The yield of methanol and hot water extract from different tea leaf were 19.60 ± 5.6 % and 20.07 ± 4.01% respectively, ( Supplementary Table S3 ). El Mannoubi states that the polarity and content of the plant material components are important considerations for selecting an adequate extraction solvent [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, other studies actually show the opposite by showing that antioxidant activity values vary significantly according to the type of solvent and do not depend on the degree of polarity of the organic solvent. [ 21 22 23 ] It is known that various extraction factors, including method, temperature, time, and solvent system, significantly influence the antioxidant quality of plant-derived products. [ 21 ] It can be said that the two extraction stages, namely, the initial extraction stage (crude ethanol extract) and fractionation, are thought to influence the characteristics of the compounds (total phenolics and total flavonoids) on the antioxidant potential of melinjo seeds.…”
Section: Discussionmentioning
confidence: 99%